Complex dielectric modulus and relaxation response at low microwave frequency region of dielectric ceramic Ba6-3xNd8+2xTi18O54 - Lee, Chian Heng; Hassan, Jumiah; Hashim, Mansor; Aziz, Raba'ah Syahidah; Mohd Saiden, Norlaily (World Scientific Publishing, 2014)
The desirable characteristics of Ba6-3xNd8+2xTi18O54 include high dielectric constant, low loss tangent, and high quality factor developed a new field for electronic applications. The microwave dielectric properties of Ba6-3xNd8+2xTi18O54, with x = 0.15 ceramics at different sintering temperatures (600–1300°C) were investigated. The phenomenon of polarization produced by the applied electric field was studied. The dielectric properties with respect to frequency from 1 MHz to 1.5 GHz were measured using Impedance Analyzer, and the results were compared and analyzed. The highest dielectric permittivity and lowest loss factor were defined among the samples. The complex dielectric modulus was evaluated from the measured parameters of dielectric measurement in the same frequency range, and used to differentiate the contribution of grain and grain boundary.